2021
DOI: 10.1109/jstars.2021.3074975
|View full text |Cite
|
Sign up to set email alerts
|

Improving Chlorophyll-A Estimation From Sentinel-2 (MSI) in the Barents Sea Using Machine Learning

Abstract: This paper addresses methodologies for remote sensing of ocean Chlorophyll-a (Chl-a), with emphasis on the Barents Sea. We aim at improving the monitoring capacity by integrating in-situ Chl-a observations and optical remote sensing to locally train Machine Learning (ML) models. For this purpose, in-situ measurements of Chl-a ranging from 0.014-10.81mg/m 3 , collected for the years 2016-2018, were used to train and validate models. To accurately estimate Chl-a, we propose to use additional information on pigme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Likewise, a neural network model named Ocean Color Net (OCN)) with match-up data sets showed to improve the Chl-a estimation on the surface and within the productive zone of the Barents Sea using satellite imagery data. 83 A new spatial window-based match-up data set was created by matching depth-integrated in situ Chl-a concentration with the multispectral remote sensing images from Sentinel-2. After the removal of the erroneous samples in the match-ups data sets based on satellite reflectance, the OCN was trained and tested with the match-ups data set.…”
Section: Biological Oceanographymentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a neural network model named Ocean Color Net (OCN)) with match-up data sets showed to improve the Chl-a estimation on the surface and within the productive zone of the Barents Sea using satellite imagery data. 83 A new spatial window-based match-up data set was created by matching depth-integrated in situ Chl-a concentration with the multispectral remote sensing images from Sentinel-2. After the removal of the erroneous samples in the match-ups data sets based on satellite reflectance, the OCN was trained and tested with the match-ups data set.…”
Section: Biological Oceanographymentioning
confidence: 99%
“…Also, the model predicted that CDOM plays a vital role in estimating the spatial-temporal distribution of Chl-a from the satellite color data. Likewise, a neural network model named Ocean Color Net (OCN)) with match-up data sets showed to improve the Chl-a estimation on the surface and within the productive zone of the Barents Sea using satellite imagery data . A new spatial window-based match-up data set was created by matching depth-integrated in situ Chl-a concentration with the multispectral remote sensing images from Sentinel-2.…”
Section: Biological Oceanographymentioning
confidence: 99%
“…In cases where data are normally fitted, the R 2 value typically falls within the range of 0 to 1. However, it is important to acknowledge that poorly fitted data can sometimes yield negative R 2 values, as demonstrated by Asim et al [162]. Their study focused on the development of a Case 2 Regional CoastColour (C2RCC)-net model for Chl-a retrieval, utilizing a match-up criterion based on C2RCC in situ Chl-a measurements.…”
Section: Factors Influencing Model Performance In Satellite-based Wat...mentioning
confidence: 99%
“…In this research, various subsets of deep learning models have been utilized, each with its own set of variants. Among the popular advanced networks for feed-forward neural networks (FNNs) are the MLP [31,40,161,162,238,240,245,248], mixture density networks (MDNs) [21,28,251,268], extreme learning machine (ELM) [30], cascade forward neural network (CFNN) [30], radial basis function neural network (RBFNN) [242], and Bayesian neural networks (BNNs) [251]. Additionally, recurrent neural networks, such as LSTM, and GRU have also gained significant popularity in this field due to their ability to handle sequential data and capture temporal dependencies [22,42,48,194,249,266].…”
Section: Machine or Deep Learning Model Choicementioning
confidence: 99%
“…Therefore, machine learning was also used to build a unified Chla inversion algorithm across water types. Among them, multilayer perceptron (MLP) (Vilas et al, 2011;D'Alimonte et al, 2012;Awad, 2014), Gaussian process regression (GPR) (Asim et al, 2021), support vector regression (SVR) (Hafeez et al, 2019;He et al, 2020;Hu et al, 2020), and random forest regression (RFR) (Cheng et al, 2021) have demonstrated potential in retrieving Chla. Several approaches that derived from neural network algorithms, including mixture density network (MDN) (Pahlevan et al, 2020), OLCI Neural Network Swarm(ONNS) (Hieronymi et al, 2017), and Case 2 Regional CoastColour (C2RCC) (Doerffer and Schiller, 2007), were used to inverse Chla concentrations for Cases I and II waters.…”
Section: Introductionmentioning
confidence: 99%